Characterization of eco-friendly polyurethane foam composites with bagasse and rice husk waste for thermal insulation applications - Mawardi, Indra; Nurdin, N.; Jannifar, A.; Hanif, Razak; Syamsuar, Syamsuar; Miswar, Miswar; Hardi, Supri; Amir, D; Desvita, Hera; Putra Jaya, Ramadhansyah (Polskie Towarzystwo Inzynierii Ekologicznej (PTIE), 2026)
Reducing the use of petrochemical-based polyurethane foams in thermal insulation applications is necessary to reduce environmental impacts. Natural fibers as fillers have emerged as promising ecological alternatives, promoting environmentally friendly and sustainable material practices. This study aimed to evaluate the mechanical and thermal properties of eco-friendly polyurethane foam composites containing bagasse fiber (BF) and rice husk (RH) waste. Rigid polyurethane foam (PUR) composites with BF and RH waste particles were prepared at different filler loading levels (20%, 30%, and 40%). Density, mechanical properties, thermal conductivity, thermal stability, and morphology of the composites were evaluated. The results showed that the density of the PUR composites with the BF and RH particles increased along with filler addition. Higher composite density led to increased thermal conductivity. The mechanical properties, bending strength, and bending modulus of the PUR composites with BF and RH were lower than those of pure PUR and decreased further with filler content. However, combining both fillers increased the mechanical properties by up to 172%. Thermal conductivity analysis indicated that thermal resistance decreases as filler content increases. However, the thermal conductivity values (0.0275–0.0393 W/mK) demonstrate competitive performance, comparable to conventional insulation materials, while supporting sustainability through waste utilization and reduced PUR consumption. This material shows strong potential as a thermal insulation solution for buildings and sustainable construction, particularly in the regions with abundant agricultural waste.